Acute larvicidal toxicity of five essential oils (Pinus nigra, Hyssopus officinalis, Satureja montana, Aloysia citrodora and Pelargonium graveolens) against the filariasis vector Culex quinquefasciatus: Synergistic and antagonistic effects. Issue 2 (April 2017) - Benelli, Giovanni; Pavela, Roman; Canale, Angelo; Cianfaglione, Kevin; Ciaschetti, Giampiero; Conti, Fabio; Nicoletti, Marcello; Senthil-Nathan, Sengottayan; Mehlhorn, Heinz; Maggi, Filippo
Abstract: Mosquito vector control is facing a number of important and timely challenges, mainly due to the rapid development of pesticide resistance and environmental concerns. In this scenario, screening of botanical resources for their mosquitocidal activity may offer effective and eco-friendly tools against Culicidae vectors. Culex quinquefasciatus Say (Diptera: Culicidae) is a vector of lymphatic filariasis and of dangerous arboviral diseases, such as West Nile and St. Louis encephalitis. In this study, the chemical composition of five essential oils obtained from different plants, namely Pinus nigra J.F. Arnold var. italica (Pinaceae), Hyssopus officinalis L. subsp. aristatus (Lamiaceae), Satureja montana L. subsp. montana (Lamiaceae), Aloysia citriodora Palau (Verbenaceae) and Pelargonium graveolens L'Hér (Geraniaceae), was investigated by GC–MS analysis. Furthermore, it was evaluated their acute toxicity on larvae of C. quinquefasciatus . Then, the most effective oils were selected, in order to focus on the potential synergistic and antagonistic effects, testing them in binary mixtures on C. quinquefasciatus larvae. Results showed that the higher effectiveness was obtained by S. montana subsp. montana essential oil (LC50  = 25.6 μL·L − 1 ), followed by P. nigra var. italica (LC50  = 49.8 μL·L − 1 ) and A. citriodora (LC50  = 65.6 μL·L − 1 ), while the other essential oils showed LC50 values higher than 90 μL·L − 1 . The larvicidal effectiveness can be enhanced by preparing simple binary mixtures of essential oils, such as S. montana  +  A. citriodora (ratio 1:1), which showed higher larvicidal toxicity (LC50  = 18.3 μL·L − 1 ). On the other hand, testing S. montana  +  P. nigra (1:1) an antagonistic effect was detected, leading to a LC50 (72.5 μL·L − 1 ) higher than the LC50 values calculated for the two oils tested separately. Overall, our results add useful knowledge to allow the employ of synergistic essential oil blends as effective, cheap and eco-friendly mosquito larvicides. Graphical abstract: Highlights: We tested binary mixtures of 5 essential oils as larvicides on Cx. quinquefasciatus . The chemical composition of 5 essential oils was studied by GC–MS. LC50 of the oils ranged from 25.6 μL·L − 1 to values higher than 90 μL·L − 1 Synergistic effects: S. montana  +  A. citriodora (1:1) led to LC50  = 18.3 μL·L − 1 . Antagonistic effects: S. montana  +  P. nigra (1:1) led to LC50  = 72.5 μL·L − 1 .